FORENSIC ANALYSIS USING AUTOPSY TO GET DELETED WHATSAPP DATA - M. Machrush Aliy Sirojjam Mushlich; Rickson Wirawan Fernando (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2022)
Nowadays, Today, crime using smartphones is increasingly massive. Prevention efforts are carried out using mobile device forensics. In this study, a test was conducted to obtain deleted WhatsApp data using Autopsy with a combined method of ISO 27037 and NIST SP 800-101 R1. The type of data that you want to get is a list of contacts, call history, text messages, pictures, videos, audio, documents, and locations; while the total data used in this study amounted to 67 data. The results of the tests that have been carried out, Autopsy was able to obtain a quantity index of 87.5% in terms of obtaining the type of data; while in terms of getting all the data, Autopsy obtained a quantity index of 95%.